An Analysis of the Importance of Vedana for Insight Meditation Practice in the Vedana Sutta - Bajrayani, Sarisa; Tongkratok, Phramaha Chit (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
This article aimed to study 1) the content and important principles in the Vedana Sutta and 2) the importance of Vedana for insight meditation practice in the Vedana Sutta. The data were gathered from Theravada Buddhist scriptures, such as the Tipitaka, the commentaries, and sub-commentaries. These were then summarized and written in a descriptive style. From the study, the findings were as follows: The teachings and essence in Vedana Sutta are that the Buddha stayed at Savatthi city, taught Bhikkhus three feelings, and Noble Eightfold Path cultivation for observing. The analysis of the importance of feelings for the development of Vipassana meditation in the Vedana Sutta revealed the three feelings that are important to the development of Vipassana meditation. It is the determination of knowing the pleasurable and unpleasurable feelings that occur on the physical and mental sides. It’s just a feeling that arises from cause and effect only. This feeling arises because of a cause and effect, remaining due to its cause and effect, and extinguished due to it. It is caused by factors that will eventually extinguish. Those who have developed insight meditation Dhamma principle in the Noble Eightfold Path, known as the middle path, will soon reach the Noble Path, Fruits, and Nibbana to be released from all suffering heaps in Samsara and reach Nibbana, which is the realm of true happiness.